New records and increasing of the geographical distribution of spiders (Arachnida: Araneae) in Bahia Stat - Boccardo, Lilian; Romão, Júlia Andrade; Brescovit, Antonio Domingos; Jucá-Chagas, Ricardo (SITIENTIBUS série Ciências Biológicas, 2010)
This paper reported four new species of spiders in the city of Lafaiete Coutinho, Bahia, Brazil, from a sample of 87 species collected with pitfall traps in fragments of caatinga and mata de cipó. In the samples, Alpaida xavantina Levi, 1988 and Mesabolivar togatus (Keyserling, 1891) have been detected, which are new records for Bahia, increasing to 306 the number of species in this state. Attacobius carranca Brescovit & Bonaldo, 2005 and Otiothops atlanticus Platnick Grismado & Ramírez, 1999 have been registered for the municipal areas, which occurrence extends the geographical distribution of these species in the state of Bahia, since they were recorded only to Barreiras, Ilhéus, Itabuna, and Una.